Human Activity Recognition for Sport Training Machines - Nikita Bazhenov; Egor Rybin; Dmitry Korzun (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2022)
Modern video surveillance systems (VSS) can recognize a person and her/his activity. A particular example of such a VSS system is the monitoring and support of human health and wellbeing during exercise with sports equipment. In this work-inprogress paper, a prototype of the VSS system is demonstrated for monitoring the movement of a person around the sport training machine. For the recognition problem we consider the following situations: a) training machine is free (no person is close to the machine); b) a person is in the area near the training machine (but not in the working area); c) a person is in the working area of training machine (but the training machine is not used); d) a person is working on the training machine. Our early experimental study evaluates the feasibility of such a VSS system.